The impact of economic burden of disease on poverty among young migrant workers: evidence from China - Chen, Yiyan; Yan, Yueping; Chen, Lijun (Frontiers in Public Health, 2025)
IntroductionThe treatment cost expenditure for family members with illness is a significant factor exacerbating poverty. Using nationally representative data concerning the migrant population, this study analyzes the impact of the economic burden from family members’ illness on poverty among young migrant workers.MethodsFirstly, we construct a multidimensional poverty index system based on five dimensions: income, education, employment, health, and livelihood,and used the A-F method for calculation. Moreover, diverging from existing studies that objectively measure the economic burden of disease, we explore an evaluation method based on subjective perceptions.ResultsThe incidence of multidimensional poverty among young migrant workers is relatively high, at 30.93%. The economic burden imposed by family members’ illnesses significantly exacerbates their risk of poverty, particularly within the 26-35 age bracket. Furthermore, compared to their male counterparts, female young migrant workers are more susceptible to the adverse effects of the economic burden of disease.DiscussionIn China, migrant workers confront numerous challenges in both their professional and personal lives, with the economic burden on their families further exacerbating their predicament. Consequently, policymakers should prioritize enhancing health insurance coverage and expanding the reach of social welfare programs to alleviate poverty and the pressures faced by young migrant workers who are the primary breadwinners.